Plateau pika burrowing and yak grazing jointly determine ecosystem greenhouse gas emissions of alpine meadow. (27th August 2022) - Wang, Yingxin; Sun, Jian; Hou, Shuaijun; Tan, Yuhui; Wang, Zhaofeng; Chang, Shenghua; Chen, Junhe; Qian, Yongqiang; Chu, Jianmin; Hou, Fujiang
Abstract: Domestic yak ( Bos grunniens ) have coexisted with plateau pika ( Ochotona curzoniae ) for thousands of and they play irreplaceable roles in shaping the structure and function of alpine meadow ecosystem. However, the mechanisms whereby the greenhouse gas (GHG) emissions change in response to the interactive effects between yak grazing and plateau pika burrowing remain unclear. In this study, we examined the response of ecosystem GHG emissions (CO2, CH4, and N2 O flux) to yak grazing and pika burrowing in alpine meadow in Zoige County, China. The GHG emissions was measured with a static opaque chamber method. Our results revealed that CO2, CH4, N2 O flux and CO2 ‐eq were significantly influenced by yak grazing and pika burrowing independently, and in conjunction. Crucially, the relative importance of pika burrowing was higher than yak grazing on a pastoral scale. Specifically, high pika burrowing led to an increase of 440.29%, and 110.72% for CO2 ‐eq relative to low pika burrowing under moderate and heavy yak grazing situations, respectively. The value of CO2 ‐eq with low pika burrowing was negative, especially under light yak grazing conditions. Furthermore, we found that GHG emissions were sensitive to plant species richness, soil temperature, soil moisture, soil organic carbon, and soil microbial factors. Structural equation modeling indicated that pika burrowing can affect CO2 ‐eq though altering soil temperature and belowground biomass under heavy yak grazing conditions and changing soil moisture and soil microbe under light yak grazing. The results of this study enrich our understanding of the role of small burrowing mammals in the carbon sequestration of alpine meadow. In the context of the carbon neutrality of alpine grassland ecosystem, small mammals' activities and their interactions with domestic livestock‐induced changes in microtopography on GHG emissions should not be neglected.